A Corpus-Based Cross-Cultural Study of Feminist Conceptual Metaphors in American and Chinese Magazines - Shi Fang, Chen (Forum for Linguistic Studies, 2025)
Existing studies on metaphors in magazines show generalized feminist conceptual metaphors. There is lack of research on how cultural values shape the construction of “woman” via feminist conceptual metaphors in different ideological contexts. This study adopts Conceptual Metaphor Theory, Social Role Theory, Intersectionality Theory, and Cultural Dimensions Theory to conduct a corpus-based comparative analysis of feminist conceptual metaphors in American and Chinese magazines. In this study, 1,098 articles with 1,664,733 words in the American magazines Ms. and Bust and 4, 182 articles with 3,631,345 words in the Chinese magazines 中国妇女 (Women of China) and 婚姻与家庭 (Marriage and Family) from July 1, 2023 to June 30, 2024. AntConc 4.2.4 and SegmentAnt 1.0.0 tools were used for analysis. Analysis involved using Collostructional Analysis and Metaphor Identification Procedure (MIP) methods. The prevailing metaphors employed in American magazines include “war” and “journey”, which serve to construct women as resistors challenging gender binaries, fighting for individual rights (political, economic, and reproductive autonomy), and acknowledging other genders. In Chinese magazines, “architecture” and “force” are dominant metaphors. These metaphors serve to portray women as fundamental pillars of the social system, emphasizing their role in national development within the context of state frameworks, and placing a strong emphasis on the concept of harmonious integration. Cross-cultural analysis reveals shared metaphors (war, architecture, and journey) but divergent contexts. Conceptual metaphors in American magazines reflect an individualism and masculinity while conceptual metaphors in Chinese magazines reflect a collectivist ideology and femininity. Conceptual metaphors in magazines actively reconstruct women’s social roles and quietly stratify the needs of intersecting identities. They shape who counts in gender equality across cultures.